Syndemic, infodemic, pandemic of COVID-19: Towards a pandemiology of emerging diseases - Naomar Almeida-Filho (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
As the basis for a theory of the co-occurrence of epidemic and pandemic processes, the article begins with a discussion of the concept of syndemic, created during the HIV/AIDS epidemic to understand the social, behavioral, and cultural components of emerging diseases, as is the case of the current COVID-19 pandemic. Secondly, the notion of infodemic is highlighted, which has great potential to better understand the impacts of the pandemic from approaches that are generally neglected in conventional epidemiological research. Third, in order to illustrate these points, a "micro-archaeological" case study of the infodemic resulting from the COVID-19 pandemic is presented, focusing on the specific situation in Brazil. Then, the correlations between scientific evidence, intervention models, and measures to control the pandemic are comparatively analyzed in different countries, as well as their adoption or rejection in the Brazilian context, which is structured by deep economic inequalities, social inequities, and health inequities.